BANYAKNYA PENJUALAN BBM DENGAN MENGGUNAKAN POM MINI TANPA DILENGKAPI IZIN DI KECAMATAN MUARA WAHAU KABUPATEN KUTAI TIMUR - Haris Suyanto (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT The 1945 Constitution of the Republic of Indonesia for the management of Natural Resources under the provisions of Article 33. Based on this provision, Law Number 22 of 2001 concerning Oil and Natural Gas was formed. This Law replaces Law Number 44 Prp. 1960 concerning Oil and Gas Mining, Law Number 15 of 1962 concerning Establishment of Government Regulations in lieu of Law Number 2 of 1962 concerning Obligations of Oil Companies to Meet Domestic Needs.It is not known that Pom Mini retailers are illegal activities and against the law and may be subject to criminal sanctions. In Law No. 22 of 2001 concerning Oil and Gas concerning criminal provisions for parties who do not have permission to carry out downstream oil business activities. This criminal provision is regulated in Article 53 of Law No. 22 of 2001 concerning Oil and Gas.